ISOLATION AND IDENTIFICACTION OF FUNGIS RHIZOCTONIA SOLANI FROM ZINNIA SEEDS, TEST ITS PATHOGENICITY AND CONTROL IT BY ENVIRONMENTALLY FRIENDLY PRODUCTS - & Juber, Saeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted to isolate the fungus Rhizoctonia solani associated with Zinnia seeds, test its pathogenicity and evaluation the effect of  alcohol extract of coontail and lotus, grapefruit extract, sea bloom 29 and Bioimmune on this pathogene. This fungus was presented in 3 samples from 11 samples and was recorded for the first time on this plant in Iraq. All the isolates caused a significant reduction in seeds germination. Isolate A22 gave the highest decrease in percentage of germination (4%). This isolate gave 100% disease incidence and 96.5% disease severity compared to control (2.5%). The percentage of germination capacity and seed germination of the seed primed with PEG solution and planted in soil inoculated by this isolate was 45%. The alcoholic extract of coontail 0.2% and Bioimmune 12% caused a significant superiority in the inhibition of this isolate . Also these two extracts caused a significant reduction in disease incidence 77.5% and 72.5% and diseasse severity 72.5% and 70% compared to control 100% and 99.38%.